OPEN INNOVATION STRATEGY APPLICATION IN WORLD AGRICULTURE: CONTRIBUTIONS FROM A LITERATURE SYSTEMATIC REVIEW - Agudo, F. L. [UNESP]; Santini Pigatto, G. A. [UNESP]; Gobbo Júnior, J. A. [UNESP]; Baptista, R. D. [UNESP]; Queiroz, T. R. [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2020)
The growing world population requires organizations to prepare themselves to serve the market with healthy foods, on a large scale, and with cleaner production processes. Innovation in the rural environment optimizes the efficiency of the agricultural chain, the soil and water resources, and generate competitive for the agents of the field. Facing this context, the objective of the article is to present the results of a systematic review of the open innovation approach in agriculture. As a result, actions of design, innovation, value chain, knowledge management, networks, and stakeholders can facilitate open innovation in agriculture. The data indicate that the research is conducted by developed countries, and in general, open innovation is addressed without specifying the type of innovation generated. The study of open innovation in agriculture is in its embryonic stage, and it is necessary to deepen theoretical and empirical research to strengthen organizations active in the sector.
APLICAÇÃO DA ESTRATÉGIA OPEN INNOVATION NA AGRICULTURA MUNDIAL: CONTRIBUIÇÕES A PARTIR DE REVISÃO SISTEMATIZADA DA LITERATURA
Keywords: Agriculture; Competition; Literature Review; Open Innovation